PERILAKU VARIETY SEEKING GENERASI Z SERTA DAMPAKNYA TERHADAP BRAND SWITCHING - Lina Budiarti; Rena Feri Wijayanti (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
Variety seeking behavior is often found in generation Z. This research aims to explore the influence of variety seeking behavior in generation Z on brand switching. This research is an explanatory research type involving 58 respondents selected using a purposive sampling technique from the population of students who use fragrance products. The criteria used in selecting respondents were that respondents purchased and used fragrance products of at least two different brands, and respondents were individuals from generation Z. The hypothesis testing technique was carried out using a simple linear regression analysis method. The research results show that generation Z's variety seeking behavior has a positive effect on brand switching.